Agapanthus orientalis: Agapanthus, African Lily, Lily of the Nile - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS)
This document is about Agapanthus orientalis, commonly known as Agapanthus, African lily, or lily of the Nile. It details the plant’s characteristics, including its large, blue, funnel-shaped flowers and coarse, strap-like green leaves. The document covers its growth habits, planting requirements, and uses in landscaping, such as mass plantings, groundcover, and accent plants. It also highlights the plant’s moderate growth rate, drought tolerance, and pest resistance, along with available cultivars and propagation methods. The document emphasizes the plant’s ornamental features and suitability for various garden settings.  Original publication date September 1999.